A monitoring of archery performance predictors among state-level archers - Sien, Lau Jiun (2023)
Archery is a sport that required a certain level of techniques, physical conditions, tactics, and psychology to perform. It is important to understand the most crucial criteria in archery to build excellent archers. Thus, this study aimed to determine the predictors of archery performance among state-level recurve archers. Eighteen state-level recurve archers were recruited from Terengganu State Sports Council and Malaysia Pahang Sports School and 13 participants (mean age = 16.23 ± 1.74) had completed the whole study protocol. Muscle activation level, draw force line, mood states, and physical fitness level of the archers were monitored predictors of archery performance in this research. The mood states of the participants were evaluated with Brunel Mood Scale Questionnaire before the scoring session. During the scoring session, the muscle activation of left deltoid muscles, left triceps muscles, right trapezius muscles, and right triceps muscles were measured with electromyography. Meanwhile, the draw force line during the anchoring and releasing was recorded with a video camera and was analysed with Kinovea motion analysis software. The archery shooting performance was based on a total score of 36 arrows shot at a distance of 70 meters. After the scoring session, the physical fitness level of the participants was measured with fitness tests including push-ups, sit-ups, handgrip test, stork stand test, back and leg test, sit and reach test, and multistage fitness test. All the parameters were measured five times, with each measurement taken at a twomonths interval. The results of the Multiple Linear Regression (MLR) revealed muscle activation level and physical fitness level can be used as a guideline in predicting the archery shooting performance. Among the muscles tested in this study, the left deltoid is the only muscle that is associated with the archery shooting performance in the fifth measurement session. Furthermore, physical fitness level also able to predict the shooting performance significantly in the first measurement session, third measurement session and forth measurement session. The physical fitness components that were associated with the archery shooting performance included left and right handgrip strength, back and leg strength, flexibility, balance, upper muscle endurance, core muscle endurance, and cardiovascular endurance. However, the mood states and the draw force line of participants are not associated with the archery performance. It is concluded that the physical fitness level and muscle activation level of the archers can predict the archery shooting performance among state-level archers.